Localization of Periodic Dyadic Functions - Lebedeva, E. A.; Chetin, Yu. A. (Journal of mathematical sciences (New York, N.Y.), 2025)
We find a characteristic of localization for periodic functions that are defined on the locally compact Cantor group and take the values in the set of complex numbers.